2021
DOI: 10.1111/jdv.17724
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, comorbidities, and healthcare utilization of patients with chronic urticaria in Germany

Abstract: Background Comprehensive data on the epidemiology and comorbidities of chronic urticaria (CU) in Germany are either limited, or not contemporary.Objectives To investigate the epidemiology of CU, overall comorbidities and healthcare resource utilized by patients with CU in Germany, using an anonymized statutory health insurance (SHI) database.Methods Anonymized SHI claims research database of the Institute for Applied Health Research, Berlin [InGef] (01 January 2015-30 September 2018) was used to analyse insure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 45 publications
(63 reference statements)
2
34
1
Order By: Relevance
“…1 In childhood, most urticaria are acute (AU), whereas chronic urticaria (CU) is less frequent than in adults. 2 Although urticaria is usually a benign condition, it is one of the common causes of admission to the pediatric emergency department (PED). 3 The main approach to urticaria is the elimination of the underlying causes; however, the exact trigger usually may remain unknown in AU and CU.…”
Section: Introductionmentioning
confidence: 99%
“…1 In childhood, most urticaria are acute (AU), whereas chronic urticaria (CU) is less frequent than in adults. 2 Although urticaria is usually a benign condition, it is one of the common causes of admission to the pediatric emergency department (PED). 3 The main approach to urticaria is the elimination of the underlying causes; however, the exact trigger usually may remain unknown in AU and CU.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective population-based cohort study in Denmark found no association between CU and cardiovascular diseases (115). On the contrary, a prospective study showed that systemic hypertension was associated with urticaria persistence (hazard ratio, 0.71; 95% CI 0.53-0.95; p = 0.02) (110), while hypertensive and lipoprotein metabolic disorders were among the more frequent reported comorbidities (43.5% and 32.1% of CU adult population respectively) in a recently published cross-sectional German study (9), and in a Swedish registry based-study (12% and 17% respectively) (116).…”
Section: Cu and Hypertension Hyperlipidemia Metabolic Syndromes And C...mentioning
confidence: 99%
“…In patients with persist CU, an increasing prevalence of inflammatory diseases was observed, indicating a possible link between inflammation and endurance of CU (125). Back pain, acute upper respiratory infections, noninflammatory disorders of the vagina, spondylosis, and gastritis were among other rare disorders detected by using the anonymized research database of the Institute for Applied Health Research in Berlin, including insured individuals with a diagnosis of CU (9).…”
Section: Cu and Other Comorbiditiesmentioning
confidence: 99%
“…Chronic urticaria (CU) is a chronic inflammatory disorder, which presents with the sudden and unpredictable appearance of wheals, angioedema, or both for longer than 6 weeks ( 1 ). CU is a female dominant disease with a higher diagnosed incidence (0.18 vs. 0.11%) and prevalence (0.62 vs. 0.37%) of females vs. males ( 2 ). Recently a meta-analysis showed that chronic spontaneous urticaria (CSU) has a point prevalence of 1.3 and 0.8% in women vs. men and chronic inducible urticaria (CIndU) shows a female: male ratio of 2:1 to 3:1 ( 3 ).…”
Section: Introductionmentioning
confidence: 99%